Human Factors in the Chemical and Process Industries : Making it Work in Practice - Edmonds, Janette (Elsevier, 2016)
Human Factors in the Chemical and Process Industries: Making it Work in Practice is a comprehensive overview of human factors within this sector, focusing on the practical application. It has been written by acknowledged industry experts from the Keil Centre, which is a leading practice of chartered ergonomics and human factors specialists, chartered safety specialists, registered occupational psychologists, and registered clinical psychologists. The book was inspired by the international human factors training course run by the Keil Centre with the IChemE, which has reached four continents across the world. The book is written for those who want a comprehensive overview of the subject, focusing on the practical application of human factors. It has been written for safety professionals, engineers and operational disciplines within industry, and those aspiring to these disciplines, who either deal with human factors issues or any aspect of the 'human element' in their core role.
6 Human factors in risk management.
Keywords: Chemical industry -- Safety measures.; elektronické knihy; electronic books